Studi Kandungan Logam Berat Merkuri (Hg) dan Prediksi Kandungan Metil Merkuri (CH3Hg) pada Organ Kerang Darah (Anadara granosa) di Kecamatan Sidayu dan Kecamatan Banyuurip, Pantai Utara Gresik, Jawa Timur [Study of Heavy Metal Content of Mercury (Hg) and Prediction Content of Methyl Mercury (CH3Hg) on The Blood Shellfish' (Anadara granosa) Organs In Sidayu and Banyu Urip District, Gresik, East Java] - Boedi Setya Rahardja; Baskara Adam Saleh; Muhammad Arief (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Oil drilling and industrial effluent that wasted through the Bengawan Solo River estuary is a source of environmental pollution in the Sidayu and Banyu Urip district, Gresik as one that produces the blood shellfish (Anadara granosa). One of the most dangerous contaminants of heavy metals is mercury. However shellfish can accumulate more heavy metals than other aquatic animals because it settle and filter their food (filter feeder) and slow to be able to avoid the effects of pollution The Aim of this study are to determine the levels of mercury and methyl mercury predictions on blood shellfish (Anadara granosa). The process of sampling was done at coastal area of Sidayu and Banyu Urip district, Gresik then performed using Atomic Absorbance readings Spectrophotometric (AAS). This is a descriptive study and the data obtained, and then continued with stoichiometric calculations to predict the content of methyl mercury. Based on the analysis of mercury and prediction of methyl mercury in the blood shellfish (Anadara granosa) organs in coastal area of Sidayu and Banyu Urip district, Gresik, has not exceeded the threshold of SNI, the value is 0.5 ppm. Mercury contamination was high in blood clam shell with the average value of 0.273 ppm and 0.293 ppm, followed by the stomach and intestines shell with an average value of 0.226 ppm and 0.281 ppm. Lowest contamination is on the organ gill, liver, and kidneys with the average value of 0.150 ppm and 0.133 ppm.